Plan de negocios para la creación de una microempresa de producción y comercialización de accesorios y uniformes para instituciones de salud, cantón Quevedo año 2013 - Vallejo Freire, Elizabeth Patricia (2014)
Very objectively what is intended with this business plan is to determine the feasibility of creating a micro- manufacturing company dedicated to the production and marketing of accessories and uniforms for healthcare institutions. For this purpose, has performed a market which has detected the main requirements that must have this plan , also were allowed to meet the high level of acceptance showing the target market before the entry of a new supplier of uniforms and health Institutions accessories . All the analysis is mainly based on results provided by the study in a group of potential prospects of the products. During the development of the paper we analyze some of the factors necessary to establish a microenterprise time as the market, competition, suppliers, physical and human resources, sales and distribution mechanisms, all these aspects will help us establishing operations for the same. After making such calculations on estimated sales, costs and expenses to a horizon of 4 years, a positive net present value of $ 7.977,69 was obtained also an internal rate of return of 27.00 % in favor, the B / C is $ 1.22. It can be concluded, therefore, that the project is profitable.